Safety and feasibility of exhaustive exercise testing for people with epilepsy - Franziska van den Bongard; Catharina Petersen; Claus Reinsberger (Epilepsy & Behavior Reports)
People with epilepsy (PWE) are encouraged to participate in exercise and be physically active, but some PWE may report exercise-associated seizures (EAS). However, there is a lack of objective tools to inform individual recommendations for physical activity and exercise participation in PWE. This study investigated the feasibility and safety of exhaustive exercise testing in PWE. 29 patients underwent an objectively and subjectively exhaustive exercise test on a bicycle ergometer and resting state EEG was obtained before and after exercise. One patient with a history of EAS experienced a seizure immediately after exercising. In patients without EAS, an asymptomatic subclinical electrographic seizure was observed in one patient, and two patients revealed interictal epileptiform discharges only after exercise. All EEG changes occurred in the setting of non-REM sleep, while the respective pre-exercise EEG recordings revealed less sleep. No seizures or significant EEG changes after exercise were observed in any other patient. EEG investigations before and after exhaustive exercise were feasible in PWE, but safety protocols need to be established, especially in patients with EAS. Investigation of a higher number of PWE with and without EAS with repeat exercise-associated EEG may provide information about the clinical utility of exercise-associated EEGs when counseling PWE.